Reformulating the Una Via Principle in the Law on Financial Sector Development and Strengthening - Djayanti; Adhari, Ade (Universitas Islam Negeri Alauddin Makassar, 2026)
Capital market law enforcement in Indonesia faces a major legal issue in the form of uncertainty regarding the application of the una via principle in determining the appropriate enforcement pathway between administrative and criminal sanctions, particularly following Constitutional Court Decision No. 59/PUU-XXI/2023, which revoked the Financial Services Authority’s (OJK) exclusive investigative authority. This situation raises issues of legitimacy as well as a disparity in evidentiary standards between the administrative and criminal legal regimes. The study’s key findings indicate that the current formulation of the “una via” principle risks creating legal defects due to an imbalance in evidentiary standards. The dominance of administrative assessments by the OJK as the initial basis for determining criminal offenses is not always aligned with criminal evidentiary standards, thereby implicating issues of proof and the effectiveness of criminal law enforcement in the capital market sector. As normative and institutional recommendations, this study proposes reformulating the una via principle through strengthening the administrative sanctions regime, developing formal coordination mechanisms between the OJK and the Police, and institutionalizing a Joint Case Assessment Committee. Additionally, the adoption of a civil penalty system based on practices in Singapore, Malaysia, and the Netherlands is recommended to enhance legal certainty and the effectiveness of capital market law enforcement.